Inductively coupled plasma emission spectrum detection method for contents of aluminum and titanium in silicon carbide
Through inductively coupled plasma emission spectral detection method, the content of aluminum and titanium in silicon carbide is quickly and accurately detected, solving the problem of difficult detection in the prior art, improving steelmaking efficiency and reducing costs.
Patent Information
- Application Number
- CN202411966411.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art is difficult to quickly and accurately detect the content of aluminum and titanium in silicon carbide, which affects the application of silicon carbide in steelmaking.
The inductively coupled plasma emission spectroscopy detection method is used to set the parameters of the inductively coupled plasma spectrometer to prepare sample solutions and standard solutions, draw working curves, and conduct detection to determine the content of aluminum and titanium.
It realizes rapid and accurate detection of the content of aluminum and titanium in silicon carbide, improves the efficiency of the steelmaking process, reduces the detection cost, and is more environmentally friendly.
Smart Images

Figure BDA0005218464650000061 
Figure BDA0005218464650000071
Abstract
Description
Technical Field
[0001] The invention relates to a method for detecting the contents of aluminum and titanium in silicon carbide, and belongs to the technical field of chemical detection and analysis. Background Art
[0002] Silicon carbide is a new type of strong composite deoxidizer that can effectively treat oxygen in molten steel during the steelmaking process, ultimately playing a role in deoxidation, shortening the deoxidation time, saving energy, improving steelmaking efficiency, improving steel quality, reducing the consumption of raw and auxiliary materials, and reducing environmental pollution.
[0003] Industrial silicon carbide is obtained by carbothermal reduction of silicon dioxide and carbon or direct reaction of silicon powder and carbon black in an inert atmosphere. Due to the inevitable introduction of some impurities in the raw materials and production process, especially aluminum and titanium as impurities, the wide application of silicon carbide in various fields is seriously affected. Therefore, it is particularly important to determine the aluminum and titanium content in silicon carbide. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides an inductively coupled plasma emission spectroscopy detection method for the aluminum and titanium contents in silicon carbide, which can quickly and accurately detect the aluminum and titanium contents in silicon carbide, has a fast detection speed, accurate data, and can improve the smelting efficiency of the factory.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is:
[0006] The inductively coupled plasma emission spectrometry detection method for aluminum and titanium content in silicon carbide includes the following detection methods:
[0007] S1. Setting parameters of inductively coupled plasma spectrometer;
[0008] S2. Prepare the silicon carbide sample into a powder sample and pass it through a 0.150 mm sieve;
[0009] S3. Dissolution of silicon carbide sample: weigh the silicon carbide sample in a platinum crucible, gradually heat it to 1000°C in a high-temperature furnace, keep it warm for 30-40 minutes, take it out, cool it, add potassium pyrosulfate and melt it at 700°C for 10 minutes until it is transparent and clear, take it out and cool it, add hydrochloric acid and hot water to leach the molten block, heat it to dissolve the molten block, cool it to room temperature, transfer it into a 200mL volumetric flask, make up to volume, shake it well, and obtain the sample solution to be tested;
[0010] S4, liquid separation: dilute the sample solution to be tested in step S3 with water to 1 / 5 of the concentration of the original solution to obtain a liquid separation sample solution to be tested;
[0011] S5. Preparation of aluminum and titanium standard solutions:
[0012] Aluminum standard solution: weigh aluminum metal that has been placed at 105°C for 2 hours and cooled to room temperature in a desiccator into a beaker, add hydrochloric acid, heat to dissolve, cool, transfer to a 1000mL volumetric flask, dilute with water, shake well to obtain an aluminum solution, and then separate and dilute the aluminum solution to obtain an aluminum standard solution; wherein, 1mL of aluminum standard solution contains 0.1mg aluminum;
[0013] Titanium standard solution: weigh high-purity titanium metal into a beaker, add hydrochloric acid, heat to dissolve, cool, transfer to a 1000mL volumetric flask, and dilute to scale with 10% hydrochloric acid, shake well to obtain a titanium solution, and then separate and dilute the titanium solution to obtain a titanium standard solution; wherein, 1mL of titanium standard solution contains 0.01mg of titanium;
[0014] S6. Curve drawing: Pipette different volumes of aluminum and titanium standard solutions, add 1 mL of (1+1) sulfuric acid respectively, dilute with water to prepare standard solutions with aluminum content of 2.0%, 1.4%, 1.0%, 0.4%, 0.2%, 0%, and titanium content of 0%, 0.01%, 0.02%, 0.04%, 0.10%, 0.14%, respectively, and use the above standard solutions to draw working curves on an inductively coupled plasma spectrometer;
[0015] S7, detection: After the working curve of step S6 is drawn, the sample solution to be tested in step S4 is immediately tested on the working curve to obtain the content of aluminum and titanium elements.
[0016] A further improvement of the technical solution of the present invention is that: the model of the inductively coupled plasma spectrometer is iCAP6300, and the resolution at 200nm is less than 0.006nm.
[0017] The further improvement of the technical solution of the present invention is that: the parameters of step S1 are set as: ignition power 1200W, cooling gas flow 12L / min, auxiliary gas 0.5L / min, peristaltic pump speed 100 rpm;
[0018] Ambient temperature 20-25 degrees Celsius; humidity 20%-80%; liquid argon purity ≥99.996%.
[0019] A further improvement of the technical solution of the present invention is that in step S3, the ratio of silicon carbide sample g: potassium pyrosulfate g: hydrochloric acid mL: hot water mL is 0.5:4:5:50.
[0020] A further improvement of the technical solution of the present invention is that the specific operation of step S4 is: accurately transfer 10 mL of the sample solution to be tested into a 50 mL volumetric flask, dilute to volume with water, and shake well to obtain the liquid separation sample solution to be tested.
[0021] A further improvement of the technical solution of the present invention is that: in the step S5 aluminum standard solution, the ratio of metallic aluminum g to hydrochloric acid mL is 1:100; the specific operation of liquid dilution of the aluminum solution is: transfer 25 mL of the aluminum solution into a 250 mL volumetric flask, dilute to the scale with water, mix well, and obtain the aluminum standard solution.
[0022] A further improvement of the technical solution of the present invention is that: in the step S5, the ratio of high-purity titanium metal g: hydrochloric acid mL is 0.1:100; the specific operation of the titanium solution separation and dilution is: transfer 25mL of the titanium solution into a 250mL volumetric flask, dilute to the scale with water, mix well, and obtain the titanium standard solution.
[0023] A further improvement of the technical solution of the present invention is that the metal aluminum and high-purity metal titanium are weighed accurately to 0.0001 g in step S5.
[0024] Due to the adoption of the above technical solution, the technical progress achieved by the present invention is:
[0025] The present invention can quickly and accurately detect the aluminum and titanium contents in silicon carbide, has a fast detection speed, accurate data, simple operation, uses a small amount of chemical reagents, has a low detection cost and is more environmentally friendly, and can also improve the smelting efficiency of the factory.
[0026] The present invention establishes working curves of aluminum and titanium contents in an inductively coupled plasma spectrometer, thereby solving the problem of detecting the aluminum and titanium contents in silicon carbide. DETAILED DESCRIPTION
[0027] The present invention is further described in detail below in conjunction with embodiments:
[0028] The inductively coupled plasma emission spectrometry detection method for aluminum and titanium content in silicon carbide is characterized by comprising the following detection methods:
[0029] S1. Set the parameters of the inductively coupled plasma spectrometer; wherein the model of the inductively coupled plasma spectrometer is iCAP6300, and the resolution at 200nm is less than 0.006nm; the parameters are set as follows: ignition power 1200W, cooling gas flow 12L / min, auxiliary gas 0.5L / min, peristaltic pump speed 100 rpm; ambient temperature 20-25 degrees Celsius; humidity 20%-80%; liquid argon purity ≥99.996%.
[0030] S2. Prepare the silicon carbide sample into a powder sample and pass it through a 0.150 mm sieve;
[0031] S3. Dissolution of silicon carbide sample: weigh the silicon carbide sample in a platinum crucible, gradually heat it to 1000°C in a high-temperature furnace, keep it warm for 30-40 minutes, take it out, cool it, add potassium pyrosulfate and melt it at 700°C for 10 minutes until it is transparent and clear, take it out and cool it, then add hydrochloric acid and hot water to leach out the molten block, heat it to dissolve the molten block, cool it to room temperature, transfer it into a 200mL volumetric flask, make up the volume, shake it well, and obtain the sample solution to be tested; wherein, the ratio of silicon carbide sample g: potassium pyrosulfate g: hydrochloric acid mL: hot water mL is 0.5:4:5:50.
[0032] S4, liquid separation: dilute the sample solution to be tested in step S3 with water to 1 / 5 of the original solution concentration to obtain a liquid separation sample solution to be tested; the specific operation is: accurately transfer 10 mL of the sample solution to be tested into a 50 mL volumetric flask, dilute to volume with water, shake well, and obtain a liquid separation sample solution to be tested.
[0033] S5. Preparation of aluminum and titanium standard solutions:
[0034] Aluminum standard solution: weigh metallic aluminum that has been placed at 105°C for 2 hours and cooled to room temperature in a desiccator into a beaker, add hydrochloric acid, heat to dissolve, and after cooling, transfer to a 1000mL volumetric flask, dilute to volume with water, shake well to obtain an aluminum solution, and then dilute the aluminum solution to obtain an aluminum standard solution; wherein, 1mL of the aluminum standard solution contains 0.1mg of aluminum; wherein, g of metallic aluminum: mL of hydrochloric acid is 1:100; the specific operation of diluting the aluminum solution is: transfer 25mL of the aluminum solution into a 250mL volumetric flask, dilute to the scale with water, mix well, and obtain an aluminum standard solution.
[0035] Titanium standard solution: weigh high-purity titanium metal into a beaker, add hydrochloric acid, heat to dissolve, cool, transfer to a 1000mL volumetric flask, and dilute to the scale with 10% hydrochloric acid, shake well, and dilute to the scale, shake well to obtain a titanium solution, and then dilute the titanium solution by separation to obtain a titanium standard solution; wherein, 1mL of the titanium standard solution contains 0.01mg of titanium; wherein, g of high-purity titanium metal: mL of hydrochloric acid is 0.1:100; the specific operation of separation and dilution of the titanium solution is: transfer 25mL of the titanium solution into a 250mL volumetric flask, dilute to the scale with water, mix well, and obtain a titanium standard solution.
[0036] S6. Curve drawing: Pipette different volumes of aluminum and titanium standard solutions, add 1 mL of (1+1) sulfuric acid respectively, dilute with water to obtain standard solutions with aluminum contents of 2.0%, 1.4%, 1.0%, 0.4%, 0.2%, and 0%, and titanium contents of 0%, 0.01%, 0.02%, 0.04%, 0.10%, and 0.14%, respectively, and use the above standard solutions to draw a working curve on an inductively coupled plasma spectrometer.
[0037] S7, detection: After the working curve of step S6 is drawn, the sample solution to be tested in step S4 is immediately tested on the working curve to obtain the content of aluminum and titanium elements.
[0038] Embodiment 1:
[0039] 1. Turn on the instrument and set the parameters of the inductively coupled plasma spectrometer.
[0040] Ambient temperature 20-25 degrees Celsius; humidity 20%-80%; liquid argon purity ≥99.996%.
[0041] Parameter settings: ignition power 1200W, cooling gas flow 12L / min, auxiliary gas 0.5L / min, peristaltic pump speed 100 rpm.
[0042] The machine is stable for more than 0.5 hours.
[0043] 2. Sample particle size
[0044] The silicon carbide sample was made into a powder sample and passed through a 0.150 mm sieve.
[0045] 3. Sample dissolution
[0046] Weigh 0.5g of silicon carbide sample into a platinum crucible, gradually heat it to 1000℃ in a high-temperature furnace, keep it warm for 30-40min, take it out, cool it, add 4g of potassium pyrosulfate and melt it at 700℃ for 10min until it is transparent and clear, take it out and cool it, then add 5mL of hydrochloric acid and 50mL of hot water to leach out the molten block, heat it to dissolve the molten block, cool it to room temperature, transfer it into a 200mL volumetric flask, dilute it to the scale with water, shake it well, and obtain the sample solution to be tested.
[0047] In the above melting process, potassium pyrosulfate decomposes into sulfur trioxide, and sulfur trioxide reacts with metal oxides in the melt to form soluble metal sulfates.
[0048] 4. Liquid separation
[0049] Accurately transfer 10 mL of the above sample solution into a 50 mL volumetric flask, dilute to volume with water, and shake well to obtain the sample solution to be tested. The element concentration in this solution is 1 / 5 of the original solution concentration.
[0050] 5. Preparation of aluminum and titanium standard solutions
[0051] Aluminum standard solution: weigh 1.000g (accurate to 0.0001g) of aluminum (superior purity) that has been placed at 105°C for 2h and cooled to room temperature in a desiccator into a beaker, add 100.0mL of hydrochloric acid, cover with a watch glass, heat to dissolve, and after cooling, transfer to a 1000mL volumetric flask, dilute to volume with water, shake well, and obtain an aluminum solution. Transfer 25mL of aluminum solution (1.00mg / mL) into a 250mL volumetric flask, dilute to scale with water, mix well, and obtain an aluminum standard solution. 1mL of aluminum standard solution contains 0.1mg of aluminum.
[0052] Titanium standard solution: weigh 0.1000g (accurate to 0.0001g) of high-purity titanium metal into a beaker, add 100mL (1+1) hydrochloric acid (volume fraction), cover with a watch glass, heat to dissolve, cool, transfer to a 1000mL polyethylene volumetric flask, dilute to scale with 10% hydrochloric acid, shake well, and obtain a titanium solution. Transfer 25mL of titanium standard solution (0.1000mg / mL) into a 250mL volumetric flask, dilute to scale with water, mix well, and obtain a titanium standard solution. 1mL of titanium standard solution contains 0.01mg of titanium.
[0053] 6. Curve drawing
[0054] Transfer different volumes of aluminum and titanium standard solutions into a group of 100 mL volumetric flasks, see Table 1, add 1 mL of (1+1) sulfuric acid respectively, dilute to the scale with water, mix well, and obtain solutions with aluminum and titanium concentrations shown in Table 2. Use this group of solutions to draw a working curve on an inductively coupled plasma spectrometer. The curve adopts linear fitting, and the linear coefficient must be greater than 0.999.
[0055] Table 1 Standard solution addition amount
[0056]
[0057] Table 2 Standard solution concentration
[0058] element 1# 2# 3# 4# 5# 6# Aluminum content% 2.0 1.4 1.0 0.4 0.2 0 Titanium content% 0 0.01 0.02 0.04 0.10 0.14
[0059] 7. Detection
[0060] After the working curve is drawn, the sample solution to be tested is immediately tested on the working curve, and the value detected by the working curve is the content of aluminum and titanium elements.
[0061] 8. Test the precision and accuracy of the method of the present invention
[0062] The method of the present invention was used to perform 10 parallel measurements on a silicon carbide standard sample No. 359, and 10 groups of aluminum and titanium content values were obtained. The results were compared and analyzed with the marked values. The results are shown in Table 3:
[0063] Table 3 Accuracy and precision analysis results
[0064]
[0065] The analysis results of aluminum and titanium in Table 3 have good reproducibility, and the range is smaller than the measurement error range specified in the national standard GBT 16555-2017 "Chemical Analysis Methods for Refractory Materials Containing Carbon, Silicon Carbide and Nitride", indicating that the precision and accuracy of the method of the present invention are good.
[0066] 9. Recovery rate test
[0067] In order to verify the accuracy of the method of the present invention, a spike recovery experiment was carried out on the silicon carbide sample according to the test method and the selected working conditions. Silicon carbide samples with different contents were selected for spike addition. The results of the spike recovery experiment are shown in Table 4.
[0068] Table 4 Sample spike recovery (n = 6)
[0069] element Determination of average value w / % Addition amount w / % Actual measurement w / % Recovery rate / % Al 0.275 0.20 0.471 98.0 Ti 0.0230 0.010 0.0333 103.0
[0070] The recovery rates of spiked aluminum and titanium are between 96.0% and 103.0%, which meets the allowable fluctuation range of method recovery in the conformity assessment GB / T27417-2017 "Guidelines for Validation and Validation of Chemical Analysis Methods" and meets the requirements for the determination of aluminum and titanium content in silicon carbide.
[0071] 10. Conclusion
[0072] The above experimental work proves that the method of the present invention is feasible, and the purpose of using a plasma spectrometer to detect the content of aluminum and titanium in silicon carbide is achieved. The method can quickly and accurately detect the content of aluminum and titanium in silicon carbide, and has good stability. The content range is less than 1%, the error is not more than 0.1%, and the content is between 1% and 5%, and the error is not more than 0.2%. The detection results of aluminum and titanium are accurate and reliable.
Claims
1. Inductively coupled plasma emission spectrometry method for detecting aluminum and titanium content in silicon carbide, characterized in that The following detection methods are included: S1. Setting parameters of inductively coupled plasma spectrometer; S2. Prepare the silicon carbide sample into a powder sample and pass it through a 0.150 mm sieve; S3. Dissolution of silicon carbide sample: weigh the silicon carbide sample in a platinum crucible, gradually heat it to 1000°C in a high-temperature furnace, keep it warm for 30-40 minutes, take it out, cool it, add potassium pyrosulfate and melt it at 700°C for 10 minutes until it is transparent and clear, take it out and cool it, add hydrochloric acid and hot water to leach the molten block, heat it to dissolve the molten block, cool it to room temperature, transfer it into a 200mL volumetric flask, make up to volume, shake it well, and obtain the sample solution to be tested; S4, liquid separation: dilute the sample solution to be tested in step S3 with water to 1 / 5 of the concentration of the original solution to obtain a liquid separation sample solution to be tested; S5. Preparation of aluminum and titanium standard solutions: Aluminum standard solution: weigh aluminum metal that has been placed at 105°C for 2 hours and cooled to room temperature in a desiccator into a beaker, add hydrochloric acid, heat to dissolve, cool, transfer to a 1000mL volumetric flask, dilute with water, shake well to obtain an aluminum solution, and then separate and dilute the aluminum solution to obtain an aluminum standard solution; wherein, 1mL of aluminum standard solution contains 0.1mg aluminum; Titanium standard solution: weigh high-purity titanium metal into a beaker, add hydrochloric acid, heat to dissolve, cool, transfer to a 1000mL volumetric flask, and dilute to scale with 10% hydrochloric acid, shake well to obtain a titanium solution, and then separate and dilute the titanium solution to obtain a titanium standard solution; wherein, 1mL of titanium standard solution contains 0.01mg of titanium; S6. Curve drawing: Pipette different volumes of aluminum and titanium standard solutions, add 1 mL of 1+1 sulfuric acid respectively, dilute with water to prepare standard solutions with aluminum content of 2.0%, 1.4%, 1.0%, 0.4%, 0.2%, 0%, and titanium content of 0%, 0.01%, 0.02%, 0.04%, 0.10%, 0.14%, respectively, and use the above standard solutions to draw working curves on an inductively coupled plasma spectrometer; S7, detection: After the working curve of step S6 is drawn, the sample solution to be tested in step S4 is immediately tested on the working curve to obtain the content of aluminum and titanium elements.
2. The inductively coupled plasma emission spectrometry detection method for aluminum and titanium content in silicon carbide according to claim 1, characterized in that: The model of the inductively coupled plasma spectrometer is iCAP6300, and the resolution at 200 nm is less than 0.006 nm.
3. The inductively coupled plasma emission spectrometry detection method for aluminum and titanium content in silicon carbide according to claim 1, characterized in that: The parameters of step S1 are set as follows: ignition power 1200W, cooling gas flow 12L / min, auxiliary gas 0.5L / min, peristaltic pump speed 100 rpm; Ambient temperature 20-25 degrees Celsius; Humidity 20%-80%; liquid argon purity ≥99.996%.
4. The inductively coupled plasma emission spectrometry detection method for aluminum and titanium content in silicon carbide according to claim 1, characterized in that: In the step S3, the ratio of silicon carbide sample g: potassium pyrosulfate g: hydrochloric acid mL: hot water mL is 0.5:4:5:
50.
5. The inductively coupled plasma emission spectrometry detection method for aluminum and titanium content in silicon carbide according to claim 1, characterized in that: The specific operation of step S4 is: accurately transfer 10 mL of the sample solution to be tested into a 50 mL volumetric flask, dilute to volume with water, and shake well to obtain the liquid separation sample solution to be tested.
6. The inductively coupled plasma emission spectrometry detection method for aluminum and titanium content in silicon carbide according to claim 1, characterized in that: In the step S5, the ratio of metallic aluminum g to hydrochloric acid mL in the aluminum standard solution is 1:100; the specific operation of the aluminum solution separation and dilution is: transfer 25 mL of the aluminum solution into a 250 mL volumetric flask, dilute to the scale with water, mix well, and obtain the aluminum standard solution.
7. The inductively coupled plasma emission spectrometry detection method for aluminum and titanium content in silicon carbide according to claim 1, characterized in that: In the step S5, the ratio of high-purity titanium metal g: hydrochloric acid mL in the titanium standard solution is 0.1:100; the specific operation of the titanium solution separation and dilution is: transfer 25 mL of the titanium solution into a 250 mL volumetric flask, dilute to the scale with water, mix well, and obtain the titanium standard solution.
8. The inductively coupled plasma emission spectrometry detection method for aluminum and titanium content in silicon carbide according to claim 1, characterized in that: In the step S5, the metal aluminum and high-purity metal titanium are weighed accurately to 0.0001 g.
Citation Information
Patent Citations
Quantitative analysis method of impurities in beta-SiC
CN105004711A
Method for measuring contents of impurity elements in silicon carbide composite material
CN106596701A
Inductively coupled plasma emission spectrum detection method for content of Fe2O3 in SiC
CN117890355A
ICP analysis method
JP2012032171A